Export competitiveness of Indian plantation crops in EU and NAFTA - Desai, Aishwarya; Manoj, Greeshma (Journal of Plantation Crops, 2025)
The proliferation of multilateral trade agreements has opened plethora of trade opportunities and increased market access for Indian plantation crops. At the same time, the emergence of low-cost producers in Latin America, Asia and Africa as well as the Non-Tariff Barriers poses as a threat for the competitiveness of India’s plantation exports. In the given context, this study attempts to assess the export potentials of the selected plantation crops to two major trade blocs i.e., European Union (EU) and NAFTA (North American Free Trade Area). The three crops analyzed in the study are tea, coffee and pepper. The export competitiveness is analysed using the Revealed Comparative Advantage Index and Trade Complementary Index, each of which reveals the competitiveness and export potentials respectively. The study reveals a strong complementary trading structure for all the three selected crops, indicating high trading potentials and gains from trade with NAFTA. Moderate competitiveness along with a high degree of complementary trading structures is observed in the case of tea exports to NAFTA and pepper exports to the European Union. The coffee exports exhibit low to nil competitive strength in both trading blocs; however, the degree of trading complementarities range from medium to high with respect to coffee trade between EU and NAFTA respectively. The study reveals that the EU is the major export destination for Indian Tea and NAFTA for Pepper and India is losing competitiveness in Coffee exports globally as well as in the concerned destinations and EU.